Pengaruh Modal Kerja, Financial Leverage, Aktivitas dan Firm Size terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015-2019 - Norfadilah Norfadilah; Bambang Sudarsono (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The purpose of this study was to see the effect of working capital, financial leverage, activity, and firm size on profitability in the food and beverage sub-sector companies listed on the Indonesian Stock Exchange (BEI) for the 2015-2019 period. The sample in this study used a sampling method of 9 companies. Based on the results of this study, it shows that the working capital variable of the WCT indicator partially has a negative and significant effect on the profitability of the ROA indicator, the Financial Leverage indicator of DER is partially negative and has not significant impact on the profitability of the ROA indicator, the Ratio Activity of the TAT indicator partially has a positive and significant effect ROA profitability indicator and firm size partially have a negative and significant effect on the profitability of the ROA indicator, while the variables of Working Capital, Financial Leverage, Activity Ratio and Firm Sise simultaneously have a significant effect on profitability.